1989
DOI: 10.1055/s-0038-1647122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Retraction on the Lysis of Human Clots with Fibrin Specific and Non-Fibrin Specific Plasminogen Activators

Abstract: SummaryThe effect of the serum content of human clots on their sensitivity to lysis with plasminogen activators was studied in a system composed of 125I-fibrin labeled clots immersed in buffer or in citrated plasma. The effect was studied with plasma clots before or after mechanical compression and with whole blood clots before or after retraction, using either the fibrin specific plasminogen activators recombinant tissue-type plasminogen activator (rt-PA) or recombinant single chain urokinase-type plasminogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 9 publications
6
57
0
Order By: Relevance
“…2. Sabovic et al [33] also found that serum-poor blood clots were more resistant to rt-PA thrombolysis and that plasminogen recruited from surrounding plasma contributes significantly to clot lysis. The extent of thrombolysis is dependent on rt-PA concentration and increases with increasing thrombolytic concentration until saturation above 0.05 mg/ml as shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…2. Sabovic et al [33] also found that serum-poor blood clots were more resistant to rt-PA thrombolysis and that plasminogen recruited from surrounding plasma contributes significantly to clot lysis. The extent of thrombolysis is dependent on rt-PA concentration and increases with increasing thrombolytic concentration until saturation above 0.05 mg/ml as shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In clinical situations, depletion of circulating plasminogen will result in the permeation of plasminogen-poor plasma into the front of the clot with a subsequent efflux out the back of the clot of fluid containing constituents of the coagulation milieu. Also, clot retraction may exude plasminogen-rich fluid from the clot (30). Under these conditions of low prevailing inner clot plasminogen concentrations and low plasmin generation, the interference of plasmin action on fibrin by excess tPA may be pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed in the 'Materials and methods' section, reperfusion with tPA was not feasible when 30% FeCl 3 was used or when tPA administration was delayed for 1 hour after FeCl 3 application possibly because size and retraction of the clot had reached a state difficult to be lysed by tPA (Sabovic et al, 1989;Sabovic and Blinc, 2000). Reperfusion was obtained with early (10 minutes after FeCl 3 ) tPA administration in 12 out of 23 mice when thrombus was induced with 10% FeCl 3 .…”
Section: Reperfusion With Tissue Plasminogen Activatormentioning
confidence: 99%